Lithium metal secondary battery

JP2025042360APending Publication Date: 2025-03-27TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023149324
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-27

AI Technical Summary

Benefits of technology

【0010】 本開示のリチウム金属二次電池によると、サイクル特性を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025042360000001_ABST
    Figure 2025042360000001_ABST
Patent Text Reader

Abstract

To provide a lithium metal secondary battery that suppresses peeling between an electrolyte layer and a lithium metal layer and has improved cycle characteristics.SOLUTION: A lithium metal secondary battery includes a negative electrode current collector layer, an alloy layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer in this order. The alloy layer contains an alloy containing indium and tin. Preferably, the battery further has a lithium metal layer between the negative electrode current collector layer and the alloy layer.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to lithium metal secondary batteries. [Background technology]

[0002] In lithium metal secondary batteries that use metallic lithium as the negative electrode active material, lithium metal is precipitated and dissolved on the negative electrode side by charge / discharge (oxidation-reduction reaction). Lithium metal has an extremely base potential and a high theoretical capacity density, so the realization of lithium metal secondary batteries is expected, and the following lithium metal secondary batteries have been disclosed.

[0003] For example, Patent Document 1 discloses a lithium metal secondary battery having a solid electrolyte layer between a positive electrode and a negative electrode, the negative electrode having a negative electrode current collector and a protective layer, the protective layer containing a metal capable of being alloyed with lithium, and having a volumetric capacity density of 1000 mAh / L or more. According to the lithium metal secondary battery of Patent Document 1, it is said that durability can be improved.

[0004] Patent Document 2 discloses an all-solid-state lithium battery constructed by joining a positive electrode, a solid electrolyte, and a negative electrode made of metallic lithium, characterized in that at least one lithium alloy layer selected from a lithium-aluminum alloy, a lithium-gallium alloy, a lithium-indium alloy, a lithium-antimony alloy, and a lithium-bismuth alloy is provided at the interface between the solid electrolyte and the lithium negative electrode. According to the all-solid-state lithium battery of Patent Document 2, there is no need to provide an extra mechanism such as applying strong pressure as in the conventional technology to maintain contact at the solid phase interface between the solid electrolyte and the Li metal negative electrode, and by simply providing a Li alloy layer at the interface between the solid electrolyte and the Li negative electrode, good contact at the interface can be maintained even during discharge at a high current density of the battery, and furthermore, since no pressure mechanism is required, it is possible to reduce the size and thickness of the battery and thereby reduce its weight. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2023-035226 A [Patent Document 2] Special Publication No. 6-101335 Summary of the Invention [Problem to be solved by the invention]

[0006] Lithium metal secondary batteries, which contain lithium metal as a negative electrode active material, are expected to have excellent battery characteristics, but their cycle characteristics are still insufficient, and there is a demand for improvements in the cycle characteristics.One of the factors that may cause the cycle characteristics of lithium metal secondary batteries to be insufficient is thought to be peeling at the interface between the electrolyte layer and the lithium metal layer.

[0007] An object of the present disclosure is to provide a lithium metal secondary battery capable of improving cycle characteristics. [Means for solving the problem]

[0008] The present disclosure achieves the above object by the following means.

[0009] Aspect 1: A lithium metal secondary battery, The lithium metal secondary battery has a negative electrode current collector layer, an alloy layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer in this order; and The alloy layer contains an alloy including indium and tin. Lithium metal secondary battery. Aspect 2: The lithium metal secondary battery according to aspect 1, further comprising a lithium metal layer between the negative electrode active material layer and the alloy layer. Aspect 3: The lithium metal secondary battery according to aspect 1 or 2, wherein the alloy containing indium and tin has a molar ratio of indium to tin of 30 / 70 to 70 / 30, in terms of the molar ratio of indium / tin. Aspect 4: The lithium metal secondary battery according to any one of Aspects 1 to 3, wherein the thickness of the alloy layer is 0.1 μm or more and 15 μm or less when the lithium metal secondary battery is in a charged state. <Aspect 5> The lithium metal secondary battery according to any one of aspects 1 to 4, wherein the electrolyte layer contains a solid electrolyte. Effect of the Invention

[0010] According to the lithium metal secondary battery of the present disclosure, the cycle characteristics can be improved. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 shows images of elements of the lithium metal secondary battery D2 of Example 2, which were obtained by cross-sectional SEM-EDX EDX mapping analysis after the initial charge at 60° C. (FIG. 1(A) shows a superposition of the elements of indium (In), tin (Sn), Fe (iron), sulfur (S), and oxygen (O), FIG. 1(B) shows In, FIG. 1(C) shows S, FIG. 1(D) shows S, FIG. 1(E) shows Fe, and FIG. 1(F) shows O). [Diagram 2] FIG. 2 shows a cross-sectional SEM image of the lithium metal secondary battery D2 of Example 2 after the first charge at 60° C. (FIG. 2(A) is a cross-sectional SEM image, FIG. 2(B) is a schematic diagram of the cross-sectional structure). [Diagram 3] FIG. 3 shows cross-sectional SEM images of the lithium metal secondary battery d1 of Comparative Example 1 after the first charge at 60° C. (FIG. 3(A) is a cross-sectional SEM image, FIG. 3(B) is a schematic diagram of the cross-sectional structure). [Figure 4] FIG. 4 shows cross-sectional SEM images of the lithium metal secondary battery d2 of Comparative Example 2 after the first charge at 60° C. (FIG. 4(A) is a cross-sectional SEM image, FIG. 4(B) is a schematic diagram of the cross-sectional structure). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the gist of the present disclosure. In addition, in the description of the drawings, the same elements are given the same reference numerals, and duplicated descriptions will be omitted.

[0013] In the present disclosure, a "composite" refers to a composition that can constitute a positive electrode active material layer or an electrolyte layer as it is or by further containing other components, and a "composite slurry" refers to a slurry that contains a dispersion medium in addition to a "composite" and can be applied and dried to form a positive electrode active material layer or an electrolyte layer.

[0014] The lithium metal secondary battery of the present disclosure may be a liquid battery containing an electrolytic solution as an electrolyte layer, or may be a solid-state battery having a solid electrolyte layer as an electrolyte layer. In the present disclosure, a "solid-state battery" means a battery using at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. The lithium metal secondary battery of the present disclosure may also be an all-solid-state battery, i.e., a battery using only a solid electrolyte as an electrolyte.

[0015] Lithium metal secondary battery The lithium metal secondary battery of the present disclosure has a negative electrode current collector layer, an alloy layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer in this order, and The alloy layer includes an alloy including indium and tin.

[0016] According to the lithium metal secondary battery of the present disclosure, the cycle characteristics can be improved.

[0017] In a lithium metal secondary battery, although not particularly limited, during charging, lithium ions move from the positive electrode (positive electrode active material) to the negative electrode, lithium metal is precipitated on the negative electrode side, and a lithium metal layer is formed. Meanwhile, during discharging, the lithium metal layer on the negative electrode side dissolves, and lithium ions move from the negative electrode (lithium metal layer) to the positive electrode.

[0018] As shown in Fig. 2, in the lithium metal secondary battery of the present disclosure containing an alloy layer containing indium and tin, after the first charge, the alloy layer 3 (lithium-indium-tin layer) into which lithium has been inserted and the lithium metal layer 2 were formed in the order of the electrolyte layer 4, the alloy layer 3 (lithium-indium-tin layer) into which lithium has been inserted, the lithium metal layer 2, and the negative electrode current collector layer 1. On the other hand, as shown in Figs. 3 and 4, in the lithium metal secondary battery containing an alloy layer containing only one of indium and tin, after the first charge, the alloy layer 3 (lithium-indium layer or lithium-tin layer) into which lithium has been inserted and the lithium metal layer 2 were formed in the order of the electrolyte layer 4, the lithium metal layer 2, the alloy layer 3 (lithium-indium layer or lithium-tin layer) into which lithium has been inserted, and the negative electrode current collector layer 1.

[0019] The alloy layer of the present disclosure contains an alloy containing indium and tin. When forming an alloy layer containing indium and tin, the alloy containing indium and tin is considered to have a plurality of indium-tin alloy phases.

[0020] From the above, it is presumed that the lithium metal secondary battery of the present disclosure, although not particularly limited thereto, specifically deposits a lithium metal layer between the alloy layer and the negative electrode current collector layer due to a plurality of indium-tin alloy phases contained in the indium and tin alloy layer during charging. Furthermore, it is presumed that the lithium metal layer specifically deposits between the alloy layer and the negative electrode current collector layer, so that peeling at the interface between the electrolyte layer and the alloy layer is suppressed during discharging, thereby improving the cycle characteristics of the lithium metal secondary battery.

[0021] <Configuration of Lithium Metal Secondary Battery> The lithium metal secondary battery of the present disclosure has, in this order, a negative electrode current collector layer, an alloy layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer.

[0022] <Negative electrode current collector layer> The material used for the negative electrode current collector layer is not particularly limited, but any material that can be used as a negative electrode current collector for a battery can be appropriately adopted. For example, stainless steel (SUS), nickel, copper, copper alloy, and these metals plated, coated, or vapor-deposited with nickel, chromium, carbon, etc. may be used, but is not limited to these.

[0023] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.

[0024] <Alloy layer> In the lithium metal secondary battery of the present disclosure, the alloy layer contains an alloy including indium and tin.

[0025] The molar ratio of indium to tin (indium / tin molar ratio) of the alloy containing indium and tin is not particularly limited, but may be 30 / 70 to 70 / 30. This molar ratio may be, but is not particularly limited, 10 / 90 to 90 / 10, 20 / 80 to 80 / 20, 25 / 75 to 75 / 25, 30 / 70 to 70 / 30, 35 / 65 to 65 / 35, 40 / 60 to 60 / 40, or 45 / 55 to 55 / 45.

[0026] The alloy containing indium and tin may further contain a metal other than indium, tin, and lithium. The molar ratio of indium and tin to the metal other than indium, tin, and lithium ((indium and tin) / (metal other than indium, tin, and lithium)) is not particularly limited, and may be 50 / 50 to 100 / 0, 60 / 40 to 100 / 0, 70 / 30 to 100 / 0, 80 / 20 to 100 / 0, 90 / 10 to 100 / 0, or 95 / 5 to 100 / 0.

[0027] The alloy containing indium and tin may further contain lithium. Although not particularly limited, the alloy containing indium and tin may be accompanied by insertion and desorption of lithium during charging and discharging of the lithium metal secondary battery.

[0028] When the lithium metal secondary battery is in a charged state, the thickness of the alloy layer may be 0.1 μm or more and 15 μm or less.

[0029] In the charged state of the lithium metal secondary battery, the thickness of the alloy layer is not particularly limited, and may be 0.01 μm or more, 0.1 μm or more, 0.2 μm or more, 0.4 μm or more, 0.6 μm or more, or 0.8 μm or more, and may be 100 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less.

[0030] The method for producing the alloy layer is not particularly limited. For example, the alloy layer can be produced by binary deposition using an ion plating method, but is not limited to this.

[0031] <Electrolyte layer> <Electrolyte layer - solid electrolyte layer> The lithium metal secondary battery of the present disclosure can be a solid-state battery, i.e., have a solid electrolyte layer as the electrolyte layer.

[0032] The solid electrolyte layer may contain, in addition to the solid electrolyte, a binder and the like as necessary.

[0033] (solid electrolyte) The material of the solid electrolyte is not particularly limited, and the solid electrolyte may be, for example, a sulfide solid electrolyte, an oxide solid electrolyte, a polymer electrolyte, or the like.

[0034] Examples of sulfide solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10 GeP2S 12), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.

[0035] An example of an oxide solid electrolyte is Li7La3Zr2O 12 , Li 7-x La3Zr 1-x Nb x O 12 , Li 7-3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x (LiPON), but is not limited to these.

[0036] The sulfide solid electrolyte and the oxide solid electrolyte may be glass or crystallized glass (glass ceramic).

[0037] Examples of the polymer electrolyte include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof.

[0038] (Binder) The binder is not particularly limited. For example, the binder may be, but is not limited to, a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), polytetrafluoroethylene (PTFE), or styrene butadiene rubber (SBR), or a combination thereof.

[0039] The thickness of the electrolyte layer may be, for example, 0.1 to 1000 μm.

[0040] <Electrolyte layer - solid electrolyte layer> The lithium metal secondary battery of the present disclosure may be a liquid battery, i.e., have an electrolyte solution as the electrolyte layer, particularly an electrolyte solution held in a separator layer.

[0041] (electrolyte) The electrolyte is not particularly limited, but preferably contains a supporting salt and a solvent.

[0042] Examples of supporting salts (lithium salts) for electrolytes having lithium ion conductivity include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6, and organic lithium salts such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, and LiC(CF3SO2)3.

[0043] Examples of the solvent used in the electrolytic solution include cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), and chain esters (chain carbonates) such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The electrolytic solution preferably contains two or more kinds of solvents.

[0044] (Separator) The battery of the present disclosure may further include a separator. The separator is not particularly limited, but may be, for example, a polyolefin-based, polyamide-based, polyimide-based, or other nonwoven fabric.

[0045] <Cathode active material layer> The positive electrode active material layer contains a positive electrode active material, and may contain a binder, a conductive assistant, and a solid electrolyte as necessary.

[0046] (Cathode active material) The material of the positive electrode active material is not particularly limited. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), lithium nickel-cobalt-manganese oxide (NCM), LiCO 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Lithium nickel-cobalt-aluminate (NCA; LiNi x Co y Al z O2), Li 1+x Mn 2-x-y M y The material may be, but is not limited to, a Li-Mn spinel substituted with a different element having a composition represented by O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn).

[0047] The positive electrode active material may have a coating layer. The coating layer is a layer containing a material that has lithium ion conductivity, is low in reactivity with the positive electrode active material and the solid electrolyte, and can maintain the shape of the coating layer without flowing even when it comes into contact with the active material and the solid electrolyte. Specific examples of materials constituting the coating layer include LiNbO3, Li4Ti5O 12 , Li3PO4, etc., but are not limited to these.

[0048] The shape of the positive electrode active material may be, for example, particulate. The average particle size (D50) of the positive electrode active material is not particularly limited, and may be, for example, 10 nm or more, or 100 nm or more. On the other hand, the average particle size (D50) of the positive electrode active material may be, for example, 50 μm or less, or 20 μm or less. The average particle size (D50) can be calculated, for example, from measurements using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM).

[0049] The thickness of the positive electrode active material layer may be, for example, 0.1 μm to 1000 μm.

[0050] (Conductive assistant) The conductive assistant is not particularly limited. For example, the conductive assistant may be VGCF (Vapor Grown Carbon Fiber), acetylene black (AB), Ketjen Black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.

[0051] For the binder and the solid electrolyte, the description in the above "Electrolyte Layer" can be referred to.

[0052] <Positive electrode current collector layer> The material used for the positive electrode current collector layer is not particularly limited, but any material that can be used as a positive electrode current collector for a battery can be appropriately adopted. For example, aluminum, stainless steel (SUS), chromium, gold, platinum, iron, titanium, zinc, etc., and these metals may be plated, coated, or vapor-deposited with nickel, chromium, carbon, etc., but are not limited thereto.

[0053] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.

[0054] <Lithium metal layer> The lithium metal secondary battery of the present disclosure may further include a lithium metal layer between the negative electrode active material layer and the alloy layer.

[0055] Although not particularly limited, the lithium metal secondary battery is configured such that during charging, lithium ions move from the positive electrode (positive electrode active material) to the negative electrode, and lithium metal is precipitated on the negative electrode side, forming a lithium metal layer. On the other hand, during discharging, the lithium metal layer on the negative electrode side dissolves, and lithium ions move from the negative electrode (lithium metal layer) to the positive electrode. For this reason, the lithium metal secondary battery may have a lithium metal layer in a charged state, and may not have a lithium metal layer in an initial state (before charging) or a discharged state, but is not limited to this case.

[0056] Although not particularly limited, the lithium metal secondary battery of the present disclosure may, in a charged state, form a lithium metal layer in which lithium metal is precipitated between the negative electrode active material layer and the alloy layer.

[0057] Examples of the shape of the lithium ion battery include a coin type, a laminate type, a cylindrical type, and a square type. EXAMPLES

[0058] The present disclosure will be described in more detail with reference to the following examples, but the scope of the present disclosure is not limited to these examples.

[0059] Example 1 <Preparation of alloy layer A1> By binary deposition using an ion plating method, an alloy layer of indium and tin was formed to a thickness of 1.0 μm on a stainless steel (SUS) foil as a negative electrode current collector, and an alloy layer A1 formed on the SUS foil was obtained. At this time, the molar ratio of indium and tin was adjusted to indium / tin=67 / 33. The molar ratio of indium and tin in the obtained alloy layer A1 was indium / tin=62 / 38.

[0060] <Preparation of electrolyte layer B1> A sulfide solid electrolyte (92.6 parts by mass), a binder (7.4 parts by mass), and an appropriate amount of butyl butyrate as a dispersion medium were mixed to prepare an electrolyte mixture slurry. The obtained electrolyte mixture slurry was applied to a release film with a coating gap of 325 μm. Next, it was pre-dried at room temperature for 3 hours, and then dried at 165° C. for 1 hour, and the coated foil on the release film that had been dried was punched out into two pieces with a diameter of 14.50 mm. Next, the coated surfaces were overlapped and pressed at 7.0 tons, and the release film was peeled off to obtain a self-supporting electrolyte layer B1.

[0061] <Preparation of Positive Electrode Active Material Layer C1> A positive electrode composite slurry was prepared by mixing nickel-cobalt-lithium aluminum oxide (NCA) (84.7 parts by mass) as a positive electrode active material, a solid electrolyte (13.4 parts by mass), a binder (0.6 parts by mass), a conductive assistant (1.3 parts by mass), and an appropriate amount of butyl butyrate as a dispersion medium. The obtained positive electrode composite slurry was applied to an aluminum (Al) foil as a positive electrode current collector with a coating gap of 225 μm, pre-dried at 60° C., and then fully dried at 165° C. for 1 hour to obtain a positive electrode active material layer C1 formed on the Al foil. The basis weight of the positive electrode active material layer C1 was 18.7 mg / cm. 2 and the design capacity is 3.0mAh / cm 2 It was.

[0062] <Preparation of lithium metal secondary battery D1> The composite layer A1 was punched out to φ14.50 mm, and the positive electrode active material layer C1 was punched out to φ11.28 mm. A solid electrolyte layer B1 was placed between the alloy layer A1 and the positive electrode active material layer C1, and laminated to form a negative electrode current collector layer, an alloy layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer. Next, this laminate was placed in a laminate film, vacuum sealed, and isostatically pressed at 392 MPa by cold isostatic pressing to obtain a lithium metal secondary battery D1. Here, aluminum (Al) was used for the positive electrode tab, and nickel (Ni) was used for the negative electrode tab.

[0063] Electrochemical measurements of lithium metal secondary battery D1 The lithium metal secondary battery D1 was restrained at 1 MPa using a constant pressure jig with a spring inserted so that the restraining pressure was constant. Next, the lithium metal secondary battery D1 was placed in a thermostatic chamber at 60°C, and a constant current (current density: 0.15 mA / cm2, equivalent to 0.05 C)-constant voltage (cutoff current density: 0.03 mA / cm2, equivalent to 0.01 C) test was performed at 60°C in a range of cutoff voltages of 4.2 V-3.0 V. Next, the lithium metal secondary battery D1 was transferred to a thermostatic chamber at 25°C, and a constant current (current density: 0.15 mA / cm2, equivalent to 0.05 C)-constant voltage (cutoff current density: 0.03 mA / cm2, equivalent to 0.01 C) test was performed at 25°C in a range of cutoff voltages of 4.2 V-3.0 V, to evaluate the cycle characteristics of the reversible capacity. The reversible capacity of the lithium metal secondary battery D1 after 20 cycles is 1.48 mAh / cm 2 It was.

[0064] Example 2 <Preparation of composite layer A2> A composite layer A2 formed on a SUS foil was obtained in the same manner as in "Preparation of composite layer A1" in Example 1, except that the molar ratio of indium and tin was adjusted to indium / tin = 50 / 50. The molar ratio of indium and tin in the obtained composite layer A2 was indium / tin = 49 / 51.

[0065] <Preparation of lithium metal secondary battery D2 and electrochemical measurement> A lithium metal secondary battery D2 was obtained in the same manner as in "Preparation of lithium metal secondary battery D1" in Example 1, except that the mixture layer A2 was used instead of the mixture layer A1. Electrochemical measurements of the lithium metal secondary battery D2 were carried out in the same manner as in "Electrochemical measurements of lithium metal secondary battery D1" in Example 1. The reversible capacity of the lithium metal secondary battery D2 after 20 cycles was 1.44 mAh / cm 2 It was.

[0066] <SEM-EDX observation of lithium metal secondary battery D2> A cross section of the lithium metal secondary battery D2 after the initial charge at 60°C was observed with a scanning electron microscope (SEM) using a secondary electron image at an applied voltage of 5 kV, and element mapping was performed by energy dispersive X-ray analysis (EDX). FIG. 1 shows the results of the EDX mapping analysis of the lithium metal secondary battery D2, and FIG. 2 shows a cross-sectional SEM image and a schematic diagram of the cross-sectional structure of the lithium metal secondary battery D2. From the SEM-EDX observation, it was confirmed that the lithium metal secondary battery D2 had an electrolyte layer 4, an alloy layer 3 (lithium-indium-tin layer) into which lithium had been inserted, a lithium metal layer 2, and a negative electrode current collector layer 1 laminated in this order after the initial charge.

[0067] Example 3 <Preparation of composite layer A3> A composite layer A3 formed on a SUS foil was obtained in the same manner as in "Preparation of composite layer A1" in Example 1, except that the molar ratio of indium to tin was adjusted to indium / tin = 33 / 67. The molar ratio of indium to tin in the obtained composite layer A3 was indium / tin = 38 / 62.

[0068] <Preparation of lithium metal secondary battery D3 and electrochemical measurement> A lithium metal secondary battery D3 was obtained in the same manner as in "Preparation of lithium metal secondary battery D1" in Example 1, except that the mixture layer A3 was used instead of the mixture layer A1. Electrochemical measurements of the lithium metal secondary battery D3 were carried out in the same manner as in "Electrochemical measurements of lithium metal secondary battery D1" in Example 1. The reversible capacity of the lithium metal secondary battery D3 after 20 cycles was 1.40 mAh / cm 2 It was.

[0069] Comparative Example 1 <Preparation of composite layer a1> Except for using only indium, a composite layer a1 formed in the shape of a SUS foil was obtained in the same manner as in “Preparation of alloy layer A1” in Example 1. The molar ratio of indium to tin in the obtained composite layer a1 was indium / tin=100 / 0.

[0070] <Preparation of lithium metal secondary battery d1, electrochemical measurement, and SEM-EDX observation> A lithium metal secondary battery d1 was obtained in the same manner as in "Preparation of lithium metal secondary battery D1" in Example 1, except that the mixture layer a1 was used instead of the mixture layer A1. Electrochemical measurements of the lithium metal secondary battery d1 were carried out in the same manner as in "Electrochemical measurements of lithium metal secondary battery D1" in Example 1. The reversible capacity of the lithium metal secondary battery d1 after 20 cycles was 1.26 mAh / cm 2 The SEM-EDX observation of the lithium metal secondary battery d1 was performed according to "SEM-EDX observation of lithium metal secondary battery D2" in Example 2. FIG. 3 shows a cross-sectional SEM image of the lithium metal secondary battery d1 and a schematic diagram of the cross-sectional structure. From the SEM-EDX observation, it was confirmed that the lithium metal secondary battery d1 had an electrolyte layer 4, a lithium metal layer 2, an alloy layer 3 (lithium-indium layer) with lithium inserted, and a negative electrode current collector layer 1 formed in this order after the initial charge.

[0071] Comparative Example 2 <Preparation of composite layer a2> Except for using only tin, a composite layer a2 formed in the shape of a SUS foil was obtained in the same manner as in "Preparation of alloy layer A1" in Example 1. The molar ratio of indium to tin in the obtained composite layer a2 was indium / tin = 0 / 100.

[0072] <Preparation of lithium metal secondary battery d2, electrochemical measurement, and SEM-EDX observation> A lithium metal secondary battery d2 was obtained in the same manner as in "Preparation of lithium metal secondary battery D1" in Example 1, except that the mixture layer a2 was used instead of the mixture layer A1. Electrochemical measurements of the lithium metal secondary battery d2 were carried out in the same manner as in "Electrochemical measurements of lithium metal secondary battery D1" in Example 1. The reversible capacity of the lithium metal secondary battery d2 after 20 cycles was 0.80 mAh / cm 2The SEM-EDX observation of the lithium metal secondary battery d2 was performed according to "SEM-EDX observation of lithium metal secondary battery D2" in Example 2. FIG. 4 shows a cross-sectional SEM image of the lithium metal secondary battery d2 and a schematic diagram of the cross-sectional structure. From the SEM-EDX observation, it was confirmed that the lithium metal secondary battery d2 had an electrolyte layer 4, a lithium metal layer 2, an alloy layer 3 (lithium-tin layer) with lithium inserted, and a negative electrode current collector layer 1 formed in this order after the initial charge.

[0073] Table 1 shows the results of electrochemical measurements of the lithium metal secondary batteries of Examples 1 to 3 and Comparative Examples 1 and 2.

[0074] [Table 1]

[0075] The lithium metal secondary batteries D1 to D3 showed higher reversible capacity after 20 cycles than the lithium metal secondary batteries d1 and d2. In other words, by using an alloy layer containing indium and tin, the cycle characteristics of the lithium metal secondary batteries D1 to D3 could be improved.

[0076] In lithium metal secondary battery D2 including alloy layer A2, after the initial charge, the alloy layer 3 (lithium-indium-tin layer) into which lithium has been inserted and the lithium metal layer 2 were formed in the following order: electrolyte layer 4, alloy layer 3 (lithium-indium-tin layer) into which lithium has been inserted, lithium metal layer 2, and negative electrode current collector layer 1. On the other hand, in lithium metal secondary battery d1 including alloy layer a1 or lithium metal secondary battery d2 including alloy layer a2, the alloy layer 3 (lithium-indium layer or lithium-tin layer) into which lithium has been inserted and the lithium metal layer 2 were formed in the following order: electrolyte layer 4, lithium metal layer 2, alloy layer 3 (lithium-indium layer or lithium-tin layer) into which lithium has been inserted, and negative electrode current collector layer 1.

[0077] When preparing an alloy layer containing indium and tin, it is believed that a plurality of indium-tin alloy phases may exist.

[0078] From the above, it is presumed that in the lithium metal secondary battery of the present disclosure, due to the multiple indium-tin alloy phases contained in the indium and tin alloy layer, a lithium metal layer is specifically precipitated between the alloy layer and the negative electrode current collector layer during charging. Furthermore, since the lithium metal layer is specifically precipitated between the alloy layer and the negative electrode current collector layer, peeling at the interface between the electrolyte layer and the alloy layer is suppressed during discharging, and thus the cycle characteristics of the lithium metal secondary battery can be improved.

[0079] While preferred embodiments of the lithium metal secondary batteries of the present disclosure have been described, those skilled in the art will recognize that modifications can be made without departing from the scope of the claims. [Explanation of symbols]

[0080] 1. Negative electrode current collector layer 2 Lithium metal layer 3. Lithium-inserted alloy layer 4 Electrolyte layer 5 Cathode active material layer 6 Positive electrode current collector layer

Claims

1. A lithium metal secondary battery, The lithium metal secondary battery has a negative electrode current collector layer, an alloy layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer in this order; and The alloy layer contains an alloy including indium and tin. Lithium metal secondary battery.

2. 2. The lithium metal secondary battery according to claim 1, further comprising a lithium metal layer between the negative electrode current collector layer and the alloy layer.

3. 2. The lithium metal secondary battery according to claim 1, wherein the alloy containing indium and tin has a molar ratio of indium to tin of 30 / 70 to 70 / 30 in terms of the molar ratio of indium / tin.

4. 2. The lithium metal secondary battery according to claim 1, wherein the thickness of the alloy layer is 0.1 μm or more and 15 μm or less when the lithium metal secondary battery is in a charged state.

5. The lithium metal secondary battery according to any one of claims 1 to 4, wherein the electrolyte layer comprises a solid electrolyte.

Citation Information

Patent Citations

  • Electrode for lithium secondary battery and lithium secondary battery

    JP2002151056A

  • Battery

    JP2007123098A

  • Metal film, anode for lithium ion battery, lithium ion battery, and manufacturing method of metal film

    JP2017071804A

  • Lithium secondary battery

    WO2022168296A1

  • Form for square pillar

    JP1994101335A